Penggunaan Media Audiovisual dalam Pembelajaran Bahasa Indonesia Studi Komparatif di MIN 1 dan MIN 2 Nganjuk - Muawanah Muawanah; Ahmad Jauhar Fuad; Diana Nur Sholihah (Universitas Maritim AMNI Semarang, 2025)
Advances in science and learning technology that support spiritual, intellectual, social, emotional, and kinesthetic aspects can develop the potential of students. With the development in the world of education, technological media is needed as an alternative to today's teaching to improve the achievement of learning objectives. The focus of this study aims to determine the planning, implementation and evaluation of learning in MIN 1 and MIN 2 Nganjuk. This type of research is qualitative. As directed by the type of qualitative research, the collected data are analyzed with the theory as presented in chapter II to obtain various interpretative descriptions according to logical and rational scientific research rules. The results of this study are the use of audiovisual media in learning in Indonesian language subjects at MIN 1 and MIN 2 Nganjuk as follows: a. Learning planning using audiovisual media in Indonesian language learning at MIN 1 and MIN 2 Nganjuk is planned coherently from learning objectives, materials, and media used. b. Implementation of the use of audiovisual media in Indonesian language learning at MIN 1 and MIN 2 Nganjuk shows that the use of audiovisual media can help teachers in delivering learning materials. c. Evaluation of teaching using audiovisual media in Indonesian language learning for teachers is done through peers as a reflection for teachers.